Production and Characterization of Green gasoline Obtained by Thermal Catalytic Cracking of Crude Palm Oil (Elaeis guineensis, Jacq.) in a Pilot Plant - Mota, Silvio Alex Pereira; Mancio, Andréia de Andrade; Borges, Luiz Eduardo Pizarro; Machado, Nélio Teixeira (Scientia Plena, 2017)
This study investigated the production and characterization of green gasoline obtained from crude palm oil (Elaeis guineensis, Jacq.), which was submitted at a process of thermal catalytic cracking in a pilot plant. The cracking reactions were carried out in a reactor of 143 L, operating in batch mode at 450ºC and atmospheric pressure, using 20% (w/w) sodium carbonate (Na2CO3) as catalyst. The organic product liquid (OLP) obtained in the cracking was submitted the distillation in laboratory scale using a column vigreux type. The results show that the yields in OLP obtained in the presence of Na2CO3 were of 65.86%, with acid value of 1.02 mg KOH/g and an elevated formation of gas residual. In relating to the green gasoline this presented a low kinematic viscosity value of 0,72 (mm2.s-1) and acid value of 1,11 mg KOH/g. GC–MS analysis indicated in chemical composition of the green gasoline a percentage of 52,78% of hydrocarbon, of these 15,78% are paraffinic compounds, 31,54% of olefin, 3,50% of naphthenic and 1,94% of aromatic compounds